Strategic cost management in e-supply chain / Yuanlue Fu - Fu, Yuanlue (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2007)
Strategic cost management of the E-supply chain is one new concept which integrates three fields: strategic cost management, supply chain management and internet application, and develops one of the most important tools about how to apply E-supply chain to the improvement of the competence in creating wealth for firm shareholders and market competitive capacity. This study has two objectives: one is to discover the cyber-value chain coordinating mechanism which is one new mechanism other than market mechanism and firm mechanism; the other one is to construct the framework model of strategic cost management accounting of E-supply chain based on the new mechanism. More specifically, this paper develops three main methods of strategic cost management (including sharing information beyond one company boundary, the synergic management of the product design, and synergic utilization and management of intellectual assets), in order to improve the competitive capacity and to solve some current problems in the cost management beyond company boundary.